Analysis of Science Literacy Profile and Development of E-Book Interactive Learning Media for Junior High School Students on Earth Structure Material - Dewangga, Naufal Syafa Aflah; Prahani, Binar Kurnia; Hariyono, Eko; Satriawan, Muhammad; Dawana, Irgy Redityo; Saphira, Hanandita Veda (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This study aims to evaluate students' science literacy profile and implement earth structure and disaster mitigation materials to improve junior high school students' science literacy. This research uses a type of introductory research that applies analysis techniques in the form of descriptive research design (DPD). The research instruments used include science literacy tests, student learning experience questionnaires, and teacher performance observations in delivering the material. This indicates that the science literacy skills of junior high school students can be further improved by using appropriate learning. Based on the results of the research obtained, the science literacy indicator ‘Designing Scientific Investigations’ received the highest score with an average of 3.275, while ‘Critically Evaluating Scientific Information’ received the lowest score of 3.206. Based on the results of the research data that has been obtained, it is concluded that students' science literacy skills still need to be improved. However, female students tend to have better science literacy skills than male students, which indicates a challenge in achieving science literacy skills at an adequate level. The indicator with the lowest level of science literacy was critically evaluate scientific information. Therefore, the study recommends the development of contextualized inquiry-based learning media and technology integration to support more effective learning, as well as training for teachers to facilitate learning that trains students' critical thinking skills.